The Volatility of the Relative Price of Commodities In Terms of Manufactures Across Exchange Regimes : A Theoretical Model - Liang, Hong. (Washington, D.C. : International Monetary Fund, 1998)
This paper investigates the relationship between the nominal exchange rate regime and the volatility of relative commodity prices. The analysis shows that the relationship depends upon both the market structure and the economic agent's perception about future exchange rate movements. When the markets for manufactured goods are less competitive than the markets for primary commodities, the volatility of relative commodity prices rises when exchange rate uncertainty increases. If demand for manufactured goods is intertemporally dependent, even a small increase in exchange rate uncertainty can result in potentially large costs in terms of increased relative commodity price instability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet